Legitimacy of the Dissolution of Beliefs by Community Organizations - I Nyoman Budiana (International Journal of Research in Community Services, 2022)
Article 28E paragraph (1) of the 1945 Constitution states "Every person shall be free to choose and to practice the religion of his/her choice, to choose one’s education, to choose one’s employment, to choose one’s citizenship, and to choose one’s place of residence within the state territory, to leave it and to subsequently return to it.” In paragraph (2), everyone has the right to the freedom to believe in his/her beliefs, to express his/her views and thoughts, according to his/her conscience. The constitutional guarantees for believers can also be seen in Article 29 of the 1945 Constitution stating that the state shall be based upon the One and Only God and the State guarantees all persons the freedom of worship, each according to his/her own religion or belief. The Constitutional Court affirms that the right to adhere to a religion or belief in God Almighty is a citizen's constitutional right, not a gift from the state. Therefore, the state is obliged to protect and guarantee the fulfillment of the rights of it’s the citizens to embrace a belief other than the six religions developed in Indonesia. However, in practice the dissolution of beliefs is actually carried out by community organizations. In this study, two things will be discussed namely: 1) What is the legal position of adherents of belief in the national legal system? 2) Do community organizations have the authority to dissolve religious beliefs? This research is normative juridical research, in which the problems in this research are analyzed qualitatively.